Designing EFL Virtual Learning: The Challenges and The Best Practices - Muliyah, Pipit; Aminatun, Dyah; Hakim, Lystiana Nurhayat (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2024)
The field of education has experienced significant changes due to technological advancements. In response to these changes, online learning has become a popular teaching mode. The COVID-19 pandemic has made online learning a mandatory approach to education. Therefore, a variety of online learning tools have been developed for use. The primary goal of this research was to explore the viewpoints of educators regarding the implementation of digital media for English language teaching amid the pandemic. This research focused on investigating the challenges and the best practices experienced by Junior High School teachers when designing EFL online learning. Three English teachers were taken as participants. Moreover, a qualitative research method was utilized. Semi-structured interviews and observation were used to collect the data, and descriptive analysis was chosen as the data analysis technique. The findings revealed that the challenges faced by teachers were their difficulties in designing effective online teaching and learning plans. In addition, the best practices experienced by the teachers and students when running virtual learning were using digital media, such as Google Classroom, Instagram, and WhatsApp. Since they were readily available, digital media facilitated students' participation in learning the English language.